2017
DOI: 10.1128/jvi.01132-16
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Serotype 5 Vaccination Results in Suboptimal CD4 T Helper 1 Responses in Mice

Abstract: Adenovirus serotype 5 (Ad5) is one of the most widely used viral vectors and is known to generate potent T cell responses. While many previous studies have characterized Ad5-induced CD8 T cell responses, there is a relative lack of detailed studies that have analyzed CD4 T cells elicited by Ad5 vaccination. Here, we immunized mice with Ad5 vectors encoding lymphocytic choriomeningitis virus (LCMV) glycoprotein (GP) and examined GP-specific CD4 T cell responses elicited by Ad5 vectors and compared them to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The replication-deficient Ad5 vectors, which possess good ability in inducing antibody and T cell response (Lee et al, 2017), are ideal tools for veterinary vaccine design given the low anti-Ad5 immunity in animals. The recombinant Ad5 virus expressing capsid proteins of foot-and-mouth disease virus (FMDV), as the most successful recombinant vaccine against FMDV to date, elicits effective antibody responses in cattle and provides complete protection from challenge in swine and cattle (Sreenivasa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The replication-deficient Ad5 vectors, which possess good ability in inducing antibody and T cell response (Lee et al, 2017), are ideal tools for veterinary vaccine design given the low anti-Ad5 immunity in animals. The recombinant Ad5 virus expressing capsid proteins of foot-and-mouth disease virus (FMDV), as the most successful recombinant vaccine against FMDV to date, elicits effective antibody responses in cattle and provides complete protection from challenge in swine and cattle (Sreenivasa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with the SP-SAd36 regimen also resulted in increased frequencies of IL-2 secreting CD4+ T cells observed in response to all peptide pools of cPvCSP and cPvMSP1. This feature may represent a significant improvement for adenoviral vectors based on a recent study by Lee et al [13] which found that vaccination with an Ad5 recombinant vector induced significantly lower frequencies of antigen-specific CD4+ TH1 cells compared to acute infection, an effect attributed low IL-2 signaling [13]. The increased IL-2 production we observed also has the potential to improve the overall T cell immunogenicity, as IL-2 promotes proliferation and differentiation of naïve CD8+ T cells and the survival of antigen-experienced T cells [52].…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviral vectored malaria vaccines have been able to improve the immunogenicity of protein-based vaccines [69] and induce protective Plasmodium -specific CD8+ T cells in pre-clinical and clinical studies [1012], but low induction of CD4+ T cell suggests further improvements to adenoviral vectors should be investigated [11]. Recent studies examining the induction of CD4+ T cells following vaccination with an Ad5 vector have shown significantly lower frequencies of antigen-specific CD4+ T cells are induced when compared to acute infection, an effect that could be attributed to lower IL-2 signaling [13]. Increasing secretion or altering post-translational modifications of adenoviral transgene products might result in improved presentation of vaccine antigens to CD4+ T cells.…”
Section: Introductionmentioning
confidence: 99%
“…As an example for such a coordinated virus choice, it has been demonstrated in a murine B16 model that reovirus for triggering a CD8 Th1-dominated immune response can be combined with a subsequent CD4 Th17 helper response by vesicular stomatitis virus to achieve a potent T-cell pool for PD-1 inhibition [ 135 ]. Adenoviruses induce strong CD8 effector memory responses with a rather moderate potential for further expansion [ 136 , 137 ] and are therefore probably better suited to amplify an immune response initiated by alternative OVs. Heterologous administration also provides an option to select vectors with immunostimulatory arming adapted to specific needs of tumor immune activation.…”
Section: Oncolytic Adenoviruses In Multi-stage Immunotherapiesmentioning
confidence: 99%